2020
DOI: 10.1002/ange.202013017
|View full text |Cite
|
Sign up to set email alerts
|

Safe, Scalable, Inexpensive, and Mild Nickel‐Catalyzed Migita‐Like C−S Cross‐Couplings in Recyclable Water

Abstract: A new approach to C−S couplings is reported that relies on nickel catalysis under mild conditions, enabled by micellar catalysis in recyclable water as the reaction medium. The protocol tolerates a wide range of heteroaromatic halides and thiols, including alkyl and heteroaryl thiols, leading to a variety of thioethers in good isolated yields. The method is scalable, results in low residual metal in the products, and is applicable to syntheses of targets in the pharmaceutical area. The procedure also features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…13 Interestingly, most successful coupling reactions have resulted from electron-deficient (hetero)aryl halides except for those in Fu's and Oderinde's studies. 9,10 The same reactivity trend was also observed in Baran's studies on DEL synthesis via Ni-catalyzed C-S bond formation 14 and Lipshutz's Ni-catalyzed migita-like C-S cross-coupling in recyclable water 15 that were disclosed very recently (Fig. 1).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…13 Interestingly, most successful coupling reactions have resulted from electron-deficient (hetero)aryl halides except for those in Fu's and Oderinde's studies. 9,10 The same reactivity trend was also observed in Baran's studies on DEL synthesis via Ni-catalyzed C-S bond formation 14 and Lipshutz's Ni-catalyzed migita-like C-S cross-coupling in recyclable water 15 that were disclosed very recently (Fig. 1).…”
Section: Introductionsupporting
confidence: 76%
“…During the past two decades, great efforts have been directed to the development of catalytic systems for coupling of (hetero) aryl halides with thiols and their equivalents [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] to assemble (hetero)aryl thioethers of high prevalence in bioactive molecules 16 and synthetic intermediates. 17 Because of their abundance, relatively low cost but low reactivity, the utilization of (hetero)aryl chlorides as coupling partners has become a reference point to assess the efficiency of newly developed catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Lipshutz and co-workers demonstrated that the well-defined complex of the type [Ni(phen) 2 Br 2 ] is more catalytically active than the plain mixing of [NiBr 2 ] and phen. [103] Furthermore, the [Ni(phen) 2 Br 2 ] complex catalyzes the CÀ S cross-coupling reactions in water in the presence of DL-αtocopherol methoxypolyethylene glycol succinate (TPGS-750-M), which acts as surfactant. Remarkably, the synthesis of a key intermediate for the Pfizer's antitumor agent axitinib was achieved in gram scale, and more important, was the fact that the residual nickel found in the axitinib precursor was 9.8 ppm, which is a value below the FDA accepted guidelines of � 25 ppm.…”
Section: Nickel Catalystsmentioning
confidence: 99%
“…Phen type ligands form robust catalysts when they are coordinated to Ni(II). Thus, Lipshutz and co‐workers demonstrated that the well‐defined complex of the type [Ni(phen) 2 Br 2 ] is more catalytically active than the plain mixing of [NiBr 2 ] and phen [103] . Furthermore, the [Ni(phen) 2 Br 2 ] complex catalyzes the C−S cross‐coupling reactions in water in the presence of DL‐α‐tocopherol methoxypolyethylene glycol succinate (TPGS‐750‐M), which acts as surfactant.…”
Section: Nickel Catalystsmentioning
confidence: 99%